"Birds of a Feather Flock Together" The Impact of Choice of Spouse on Family Labor Income Inequality - Iulie Aslaksen; Tom Wennemo; Rolf Aaberge (Statistics Norway, Research Department, 2000)
This paper discusses the effects of the substantial rise in labor force participation of married women on the level, structure and trend in family labor income inequality. An interesting question is to what extent the rise in women's labor force participation has led to a tendency of "flocking together", i.e. whether women with high labor income are married to men with high labor income, or vice versa. Based on the decomposition of the Gini coefficient and a related index for the extent of "flocking together" applied to income data for Norway for the period 1973-1997 we find a tendency of "flocking together" for couples with at least one labor income and couples with two labor incomes. For couples with only one labor income (i.e. couples where only one labor income is above the threshold given by the statistical definition of labor income) the decomposition of the Gini coefficient indicates that there is no tendency of "flocking together". For this group women's labor income gives an equalizing contribution to family labor income inequality. This illustrates the importance of distinguishing between one- and two-income families in analysis of family labor income inequality.
Keywords: D31; 330; Family income distribution; decomposition of the Gini coefficient; summary measure for the extent of "flocking together".